The response of thermocline ventilation to variability at the ocean surface from observations and offline tracer modeling - Shao, Andrew Edward (2016)
Thesis (Ph.D.)--University of Washington, 2016-03 Variability in oceanic ventilation can arise from either changes at the surface of the ocean or the ocean interior. Four studies are presented which advance our understanding on how these changes can be diagnosed in both observational and modeling contexts. Chlorofluorocarbons (CFCs) and sulfur hexafluoride (SF6) have been used extensively to infer transit time distributions (TTDs) and ventilation ages in the ocean. An offline tracer model (Offtrac) is combined with a simple model of gas exchange to simulate the mixed layer saturations of CFC-11, CFC-12, and SF6. The large wintertime undersaturations of these tracers arise from the increase in solubility due to the cooling of the mixed layer and also from the entrainment of relatively tracer-poor waters as the mixed layer deepens. In the mode waters of the North Pacific, this can cause a bias TTD mean ages of up to 24%. The Antarctic Circumpolar Current (ACC) is a strong dynamical feature in the Southern Ocean which transports water around the entirety of the Antarctic continent. Monte-Carlo simulations of a meandering Gaussian jet model in conjunction with distributions of sea level anomaly from 1992 to 2014 are used to determine the mean position and width of the fronts that form the boundaries of the ACC. The mean position of these fronts largely follow the underlying topography. Significant internannual variability in the location of the fronts was uncorrelated to changes in the Southern Annular Mode (SAM). Offtrac is used to simulate CFCs, SF6, oxygen, ideal age, and transit time distributions using a boundary impulse response technique (TTD-BIR). The output from these simulations are used to evaluate how well tracers can constrain the timescales of oceanic ventilation. The inverse Gaussian solution to the 1d transport equation is shown to be a reasonable approximation to the TTD-BIR within the ventilated thermocline of the subtropical gyres, but a poor approximation in regions with strong gradients in ...